EVALUATION OF RECITATION PROGRAM PESANTREN STUDENT OF AL ASYARIAH MANDAR UNIVERSITY THROUGH THE KIRK PATRICK MODEL - Saifuddin, Saifuddin; Malik, Abdul Malik; Muh. Nur Akbar Rasyid; Sitti Mania (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2025)
The research results show that the recitation program is effective in increasing Islamic knowledge, such as fiqh, recitation and morals, as well as building student character based on the values ??of tolerance and pluralism. However, there are obstacles related to facilities and infrastructure, as well as variations in teaching methods that need to be improved. The research conclusion states that this program is relevant to student needs and supports the university's vision of building an Islamic-based intellectual generation. This program strengthens students' ability to read the Koran and basic understanding of religion, although it still requires improvement in aspects of implementation and ongoing evaluation. The research recommends developing interactive learning methods, improving facilities, and further training for presenters. Implementation of further programs such as preacher training and student study communities is also proposed to strengthen the sustainability of the program's impact.